A. \({P_n} = A_n^n\)
B. \(C_n^k = C_n^{n - k}\)
C. \(A_n^k = \frac{{n!}}{{k!}}\)
D. \({P_k}.C_n^k = A_n^k\)
C
+ Ta có \({P_n} = n!;A_n^n = \frac{{n!}}{{\left( {n - n} \right)!}} = n! \Rightarrow {P_n} = A_n^n\) nên A đúng
+ \9C_n^k = C_n^{n - k}\) (tính chất) nên B đúng.
+ \(A_n^k = \frac{{n!}}{{\left( {n - k} \right)!}}\) nên C sai.
+ \({P_k}.C_n^k = k!.\frac{{n!}}{{k!\left( {n - k} \right)!}} = \frac{{n!}}{{\left( {n - k} \right)!}} = A_n^k\) nên D đúng.
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247